2021
DOI: 10.3389/fpsyg.2021.705116
|View full text |Cite
|
Sign up to set email alerts
|

Piano Education of Children Using Musical Instrument Recognition and Deep Learning Technologies Under the Educational Psychology

Abstract: The objective of the study was to enhance quality education in the traditional pre-school piano education. Deep Learning (DL) technology is applied to piano education of children to improve their interest in learning music. Firstly, the problems of the traditional piano education of children were analyzed with the teaching patterns discussed under educational psychology, and a targeted music education plan was established. Secondly, musical instrument recognition technology was introduced, and the musical inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One area where technology has been utilised is in piano education for children. Li (2021) conducted a study on piano lessons using deep learning technology and found that it had practical value. This suggests that technology could augment the learning experience for children in music education.…”
Section: Live Performance and Stage Technologiesmentioning
confidence: 99%
“…One area where technology has been utilised is in piano education for children. Li (2021) conducted a study on piano lessons using deep learning technology and found that it had practical value. This suggests that technology could augment the learning experience for children in music education.…”
Section: Live Performance and Stage Technologiesmentioning
confidence: 99%
“…Yu Zhao 1* , WenWen Gao 2 & ShanShan Ku 3 An ever-growing portion of the economy is dedicated to the field of education, intensifying the urgency of identifying strategies to secure the sector's enduring prosperity and elevate educational standards universally. This study introduces a model for enhancing games and optimizing data analysis within the context of early childhood education (ECE) majors, hinging on deep learning (DL).…”
Section: Optimization Of the Game Improvement And Data Analysis Model...mentioning
confidence: 99%
“…Deeplearning4J mainly uses data parallelization solutions. Currently, Deeplearning4J supports two data parallelization strategies: a parameter synchronous averaging and a decentralized gradient sharing scheme [21]. e principle of data parallelization is shown in Figure 4.…”
Section: Backpropagation Algorithmmentioning
confidence: 99%